Factors Influencing Consumer's Choice of Streaming Over the top (OTT) Platforms - Ghalawat, Suman; Yadav, Ekta; Kumar, Mohit; Kumari, Neelam; Goyal, Megha; Girdhar, Amita; Agarwal, Subodh (Indian Journal of Extension Education, 2025)
With the rapid advancement in technology, the penetration of smartphones and the increase in levels of affordable internet facilities have resulted in the rise of OTT media services. OTT platforms give freedom to their users to watch T.V. series, movies, etc at their own convenience. The study was conducted to find out the factors influencing consumers' choice of streaming OTT platforms. A convenience sampling technique was used for the study and responses from 200 respondents (students, working people/ staff, homemakers, and entrepreneurs) were collected in Hisar city, through a semi-structured questionnaire. The variations in the factors (Growth, Benefits of OTT, Integrated marketing and communication) were 41.321, 6.621, 5.977, and 5.378 per cent, respectively. As per factorÂ analysis, all four factors were the most important that influenced consumers' choice of streaming OTT services, and the Cronbach alpha values were 0.844, 0.812, 0.798, and 0.629 , respectively.